Asynchronous H∞ filtering of continuous‐time Markov jump systems. (12th November 2019) - Fang, Mei; Dong, Shanling; Wu, Zheng‐Guang
Summary: The paper investigates the asynchronous H ∞ filtering design problem for continuous‐time linear systems with Markov jump. The hidden Markov jump principle is applied to represent the asynchronous situation between the target system and the designed filter. Via a Lyapunov technique, two sufficient conditions are developed to guarantee that the filtering error system is stochastically stable with a prescribed H ∞ noise attenuation level. Furthermore, three filtering design approaches are developed in the form of linear matrix inequalities. Finally, one example is provided to show the effectiveness and feasibility of the developed methods.